PRESTASI AKADEMIK DITINJAU DARI LINGKUNGAN PEMBELAJARAN - Ghufron, M.Nur (Pascasarjana IAIN Kudus, 2013)
The goal of this research was to examine the relationship between Constructivist learning environments and academic achievementof Psychology among students. The hypotheses tested in thisresearch were: there were differences of academic achievementbetween students taught by constructivist learning environmentsand conventional learning environment. The instruments used inthis research were constructivist learning environments scale andconventional learning environment scale. The total of the samplewas 71 students taken from Tarbiyah Major Islamic education ofKudus State Islamic High School. Class A that used constructivistlearning environments and Class B that used conventional learningenvironments. The results of data analyses show that: there weresignificant differences between students of class A that usedconstructivist learning environments from Tarbiyah Major Islamiceducation of Kudus State Islamic High School and class B thatused conventional learning environments from Tarbiyah Major Islamic education of Kudus State Islamic High School on their academic achievement.